2021
DOI: 10.1177/00111287211041521
|View full text |Cite
|
Sign up to set email alerts
|

Are Asian Victims Less Likely to Report Hate Crime Victimization to the Police? Implications for Research and Policy in the Wake of the COVID-19 Pandemic

Abstract: Anti-Asian hate crimes have increased during the COVID-19 pandemic. Yet, no research has considered whether crime reporting patterns are different among Asian hate crime victims, relative to other victims. Following this, this research presents an examination of differences in reporting victimization to the police between Asian and non-Asian victims using information from 997 respondents who experienced a hate crime in the first 1 to 2 months of the pandemic. Results indicate that Asian victims are significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 64 publications
(99 reference statements)
0
46
0
Order By: Relevance
“…Although prior research has focused exclusively on the role of anti-Black (Cabeldue et al, 2018; Dunbar & Molina, 2004) and antigay, antisexual orientation, and antitransgender attitudes (Cabeldue et al, 2018; Cowan et al, 2005) in predicting support for hate crime legislation, the current research follows–and builds on–prior researching by finding that anti-Hispanic, anti-Asian, and anti-Black prejudice are all significantly and negatively associated with hate crime law support. We note that, while prior research has largely neglected anti-Asian prejudice, the consideration of this specific form of prejudice is likely particularly relevant right now, given the prevalence in such sentiment during the COVID-19 pandemic (Lantz & Wenger, 2021). Our findings regarding the direct relationship between each of these different prejudicial attitudes are important because they provide more evidence that opposing hate crime legislation may allow prejudiced individuals to subtly express their negative beliefs about members of minority groups (Cabeldue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although prior research has focused exclusively on the role of anti-Black (Cabeldue et al, 2018; Dunbar & Molina, 2004) and antigay, antisexual orientation, and antitransgender attitudes (Cabeldue et al, 2018; Cowan et al, 2005) in predicting support for hate crime legislation, the current research follows–and builds on–prior researching by finding that anti-Hispanic, anti-Asian, and anti-Black prejudice are all significantly and negatively associated with hate crime law support. We note that, while prior research has largely neglected anti-Asian prejudice, the consideration of this specific form of prejudice is likely particularly relevant right now, given the prevalence in such sentiment during the COVID-19 pandemic (Lantz & Wenger, 2021). Our findings regarding the direct relationship between each of these different prejudicial attitudes are important because they provide more evidence that opposing hate crime legislation may allow prejudiced individuals to subtly express their negative beliefs about members of minority groups (Cabeldue et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While not directly comparable because of differences in data collection, the relative similarity in the total number of hate crimes across two data sources (112, compared to 158), given that one data source represents the entire country (i.e., FBI statistics) and another represents only a small proportion of the Asian population in America (i.e., the current study), is notable. Official hate crime statistics clearly represent only a fraction of hate crimes that actually occur, and some recent research has suggested that Asian victims may be particularly unlikely to report hate crime victimization ( Lantz & Wenger, 2021 ). Future research should continue to explore the reporting patterns of Asian hate crime victims in greater depth.…”
Section: Discussionmentioning
confidence: 99%
“…Wu [ 40 ] notes that although a growing number of studies address gender and racial/ethnic biases, there is a lack of data on AAPI youth, and young adults are highly vulnerable to the negative effects of racism on mental health and identity development. Additionally, tweeters highlight the importance of collecting data on hate crimes; relevant data has long been underreported because distrust of law enforcement, language barriers, and immigration status are deterrents to reporting a crime [ 41 ]. In addition, law enforcement agencies often aggregate reports by ethnicity, lumping incidents against specific groups into broader racial categories [ 42 ], which can obscure important patterns and unique challenges encountered by racially minoritized groups such as AAs.…”
Section: Discussionmentioning
confidence: 99%